Physiology and transcriptome analysis of the response mechanism of Solidago canadensis to the nitrogen addition environment - Wu, Miao; Liu, Huiyuan; Zhang, Ying; Li, Bingbing; Zhu, Tao; Sun, Man (Frontiers in Plant Science, 2023)
Solidago canadensis is an invasive plant that can adapt to variable environmental conditions. To explore the molecular mechanism of the response to nitrogen (N) addition conditions in S. canadensis, physiology and transcriptome analysis were performed with samples that cultured by natural and three N level conditions. Comparative analysis detected many differentially expressed genes (DEGs), including the function of plant growth and development, photosynthesis, antioxidant, sugar metabolism and secondary metabolism pathways. Most genes encoding proteins involved in plant growth, circadian rhythm and photosynthesis were upregulated. Furthermore, secondary metabolism-related genes were specifically expressed among the different groups; for example, most DEGs related to phenol and flavonoid synthesis were downregulated in the N-level environment. Most DEGs related to diterpenoid and monoterpenoid biosynthesis were upregulated. In addition, many physiological responses, such as antioxidant enzyme activities and chlorophyll and soluble sugar contents, were elevated by the N environment, which was consistent with the gene expression levels in each group. Collectively, our observations indicated that S. canadensis may be promoted by N deposition conditions with the alteration of plant growth, secondary metabolism and physiological accumulation.